THE QUALITY OF SOAKING LAMB MEAT WITH BATAK ONION EXTRACT (Allium chinense G. Don) - Asmaq, Nur; Wibowo, Fachrina (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study aims to determine lamb meat quality with Batak onion extract (A. chinense G. Don). The samples used in this study were Batak onions (A. chinense G. Don) and lamb. This study used an experimental method with a factorial completely randomized design with a 4 x 3 x 2 pattern. Factor A was the concentration of Batak onion extract (BOE), namely A0: without treatment, A1: 10% and A2: 20%, while factor B is the length of immersion, namely B0: 0 hours, B1: 1 hour and B2: 2 hours. Parameters observed in this study were water content, cooking loss and total bacterial colonies of lamb. The results obtained in this study showed that the analysis of variance for each variable was very significantly different (P<0.01) so it was continued using the Duncan Multiple Range's Test (DMRT) further test. Further test results showed a significant interaction (P<0.05) between Batak onion extract and soaking time on the observed parameters. The best values ​​of water content, pH and total colony were in treatment A2B1 with a value of 76.92%, 6.9 and A2B1 6 x 10 3 CFU/g, while the best cooking loss value was in treatment A1B1 with a value of 48%.